Associer les acteurs de terrain à l’observation de la fréquentation et des pratiques récréatives en montagne : enseignements à partir de deux projets collaboratifs en France et en Suisse - Christophe Clivaz (Institut de Géographie Alpine, 2021)
The Alps are particularly affected by the effects of climate change. The average temperature increase is twice as high as that observed at the global level (Beniston, 2012). Climate change is having a profound impact on tourism, sports and, more broadly, recreational activities in mountain regions. First of all, this concerns the rise in the rain-snow limit and the increasing scarcity of snow (Gonseth, 2013), leading ski lift companies to invest heavily in the production of artificial snow in order to sustain the activities of skiing and snowboarding (Abegg, 2011; Clivaz et al., 2015). However, climate change also has important repercussions for other sports and recreational pursuits in these regions, especially in summer (hiking, climbing, mountaineering, etc.). Observing the effects of climate change on recreational activities in less-developed mountain regions proves complex. In this context, an exploratory participatory research-action project, presented in this paper, was carried out in 2019 with the objective of both taking stock of existing data on the use of less-developed mountain regions and studying the feasibility of an approach involving field actors in the observation of the evolution of this use. This contribution is an opportunity to look back at this project and to show the challenges and difficulties linked to this deliberately collaborative approach, in particular by putting it into perspective with the French observation program “Refuges Sentinelles” (RS) (Sentinel Hut Program) from which it was inspired. More generally, it is also a question of examining the knowledge issues, for both research and field actors (hut keepers, mountain guides and leaders), linked to a collaborative research approach. The results in terms of data collected or issues identified (changes in visitor flows, the role of hut keepers, types of clientele, etc.) are not part of the subject of this contribution, even if they are mentioned from time to time in order to illustrate the topic.Our methodology is based on the final report of the participatory research-action project we conducted (Obin et al., 2020), on a student thesis on the feasibility of the Sentinel Hut program and of the approach to be implemented (Berthet, 2014), as well as on the minutes of various sessions and events related to this program. We supplemented these sources with a semi-structured interview conducted online in January 2021 with the scientific leader of this program, focusing specifically on the theme of the collaborative methodology utilised.